Influence of substrate diffusion on degradation of dibenzofuran and 3-chlorodibenzofuran by attached and suspended bacteria. - Harms, H (1994)
Dibenzofuran uptake-associated kinetic parameters of suspended and attached Sphingomonas sp. strain HH19k cells were compared. The suspended cells were studied in a batch system, whereas glass beads in percolated columns were used as the solid support for attached cells. The maximum specific activities of cells in the two systems were the same. The apparent half-maximum uptake rate-associated concentrations (Kt') of attached cells, however, were considerably greater than those of suspended cells and depended on cell density and on percolation velocity. A mathematical model was developed to explain the observed differences in terms of substrate transport to the cells. This model was based on the assumptions that the intrinsic half-maximum uptake rate-associated concentration (Kt) was unchanged and that deviations of Kt' from Kt resulted from the stereometry and the hydrodynamics around the cells. Our calculations showed that (i) diffusion to suspended cells and to single attached cells is efficient and therefore only slightly affects Kt'; (ii) diffusion to cells located on crowded surfaces is considerably lower than that to single attached cells and greatly increases Kt', which depends on the cell density; (iii) the convective-diffusive transport to attached cells that occurs in a percolated column is influenced by the liquid flow and results in dependency of Kt' on the flow rate; and (iv) higher specific affinity of cells correlates with higher susceptibility to diffusion limitation. Properties of the experimental system which limited quantitative proof of exclusively transport-controlled variations of Kt' are discussed.